Peaking in team sports - Mujika, I. (FINA World Sports Medicine Congress, 18, 2016)
Dr. Inigo Mujika, (ESP) talks about "Peaking in Team Sports (or, Let`s do the WIST: Sport Science to Enhance Water Polo)" at the FINA World Sports Medicine Congress 2016 (23:58 min).